Speaking Proficiency in TEFL: Utilizing the Use of Omegle Application - Attallah, Syifa Putri (English Education Department, 2025)
This research aimed to explore the extents in which Omegle application was effective to improve students’ speaking proficiency levels. The study was held in the academic year of 2023/2024 at SMPT Darussalam, Reni Jaya, Bojong Sari, Depok by involving 36 students of 7th grade, occupied in one class. The method employed in this study was quantitative with descriptive statistics approach. The data were gathered by using speaking pre- and post-tests. These data were analysed quantitatively by finding out each student’s speaking outcome in each test to be classified into speaking proficiency levels; ‘excellent’, ‘good’, ‘moderate’, ‘poor’. Then, the results were used to determine students’ speaking proficiency level and reported in percentages. The findings revealed that the utilization of Omegle application as learning media was effective to improve students’ speaking achievement in which in the pre-test, majority of the students (16) fell into ‘poor’ level (44.4%), while in the post-test, most of them (14) were in ‘moderate’ level (38.8%). Additionally, in the pre-test, none of the student was ‘excellent’ (0%) whereas in the post-test, 8 students were ‘excellent’ (22.2%). Based on these findings, this study deduced that utilizing Omegle as learning media was effective to improve students’ speaking proficiency levels.